Metakaolin-Based and Blast Furnace Slag-Activated Geopolymer Cement with Waste Powders - Kabirova, Aigul; Husem, Metin; Dilbas, Hasan; Uysal, Mucteba; Canpolat, Orhan (SPRINGER INT PUBL AG, 2023)
Sustainability leads a cementless materials branch in material engineering and science. Geopolymer is one part/leaf of the sustainability branch and has many advantages (i.e., less carbon emission and low energy consumption in production) attracting attention itself. The recent dizzying progress observed in geopolymers has now turned its direction towards environmentally friendly waste-based geopolymers. Accordingly, many types of waste produced in various industries have come to life in geopolymer seeming like a positive approach from the environmental point of view. However, this area is still a virgin and is worth studying. Hence, to contribute to this field, this experimental study was conducted. Accordingly, 25-50-75% basalt powder (BP), limestone powder (LSP), recycled aggregate powder (RAP), and waste marble powder (WMP) (< 63 mu m) were employed in the experiments to produce a durable and sustainable metakaolin (MK) based geopolymer with blast furnace slag (BFS). Thirteen mixtures were produced, and reference was included in the experiments. The main binder as a composition of MK, BFS, and an activator (1:2 NaOH/Na2SiO3) was considered. At the first stage of the experiments, the main properties of the geopolymer mortars were determined by conducting the tests of the mechanical properties and the physical properties. Then, the tests of the durability properties were applied to the reference and the best geopolymer specimens selected by different multi-criteria decision support methods (MCDMs). In this point, CDMs are useful tools to find the best choice and two MCDMs, such as TOPSIS and HDM, were considered to obtain the best geopolymer mix. As a result, ages-based evaluation showed that 28-day-old specimens had the high results. BP provided satisfactory results with a dense and compact structure in geopolymer. The best geopolymer mixture included 75% BP and had a significant mechanical and durability performance compared to reference with satisfactory properties. Examining the experimental results with a MCDM may give excellent results than the conventional singular evaluation technique.
Keywords: Metakaolin-based geopolymer; Waste powder; Mechanical properties; Durability properties; RECYCLED AGGREGATE CONCRETE; MECHANICAL-PROPERTIES; ASH; PERFORMANCE; DURABILITY; STRENGTH; BEHAVIOR; Engineering